ANALISIS KESULITAN BELAJAR MATEMATIKA MATERI BENTUK ALJABAR PADA SISWA SMP KELAS VII - Nurlela Nugraha; Gida Kadarisma; Wahyu Setiawan (Departement of Mathematics Education, 2019)
This study aims to determine what difficulties experienced by students in working on the problems in algebraic material and what factors cause students to experience difficulties in working on the questions in algebraic material. This type of research is a descriptive research method with a qualitative approach. The research subjects used were students of Grade 1 Pearl Junior High School 1 as many as 30 students. The data collection technique is a description test of 5 items, interviews, and student assignment documentation. The results of this study found that student learning difficulties can be seen from four errors in working on algebraic problems, namely lack of understanding of positive and negative operations, lack of understanding of reading questions, errors in calculations, use of wrong processes. Factors that cause student errors in spelling out algebraic problems are incorrect writing the operating symbol, forgetting the results of the operation of positive and negative signs, not being careful and concentrating, forgetting about the material taught before because they did not study, not understanding the teacher's explanation, not ready if there test, do not understand/ misunderstand the intended question, hurry to work on the problem.